若序列x(n)的Z变换为[img=39x20]18034a9cb6bae81.jpg[/img],则[img=78x30]18034a9cbf044d2.jpg[/img]的Z变换为
A: [img=59x20]18034a9cc7b2137.jpg[/img]
B: [img=68x20]18034a9cd1230d7.jpg[/img]
C: [img=49x20]18034a9cda48dcd.jpg[/img]
D: [img=59x20]18034a9ce33a042.jpg[/img]
A: [img=59x20]18034a9cc7b2137.jpg[/img]
B: [img=68x20]18034a9cd1230d7.jpg[/img]
C: [img=49x20]18034a9cda48dcd.jpg[/img]
D: [img=59x20]18034a9ce33a042.jpg[/img]
举一反三
- 若序列x(n)的Z变换为[img=39x20]18034a9cb6bae81.jpg[/img],则[img=78x30]18034a9cbf044d2.jpg[/img]的Z变换为 未知类型:{'options': ['', '', '', ''], 'type': 102}
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]1803da40b5dbfd6.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]1803da40ac7a8ce.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]1803381b293bffb.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32
- X为随机变量,E(X)=-1,D(X)=3,则E(3[img=24x22]17de66bf652c147.png[/img]+20)=( ) A: 18 B: 9 C: 30 D: 32